Geomorphology of the Mt. Cusna Ridge (Northern Apennines, Italy): evolution of a Holocene landscape. Issue 2 (13th November 2018) - Mariani, Guido S.; Cremaschi, Mauro; Zerboni, Andrea; Zuccoli, Luisa; Trombino, Luca
ABSTRACT: The Mt. Cusna ridge, located in the Northern Apennines (North Italy), is a mountain area of relevant geological interest for the interaction through time of distinct geomorphic processes, acting since the end of the Last Glacial Maximum. A geomorphological map at the 1:10, 000 scale was produced to characterise the main landforms and processes identifiable on the ridge. From this, a detailed reconstruction of the Holocene landscape history of the area is drawn. After deglaciation, at the end of the Pleistocene, glacial and periglacial processes left wide deposits and barren surfaces. Slope and running water processes acted cyclically on the landscape through phases of stronger slope denudation and landslide activation followed by stability periods. These processes are related to the main climatic changes recorded for the N Apennines during the Holocene. Since the Late Holocene, the impact of human communities may have played a prominent role as an agent of landscape modification.